A Report On The Secretary's Advisory Committee - Coal Mine Safety Research - Cloyd D. McDowell (Society for Mining, Metallurgy & Exploration, 1973)
The Federal coal Mine Health and Safety Act of 1969 has been criticized by those who say it goes too far in controlling the activity of private enterprise and by those who say it does not go far enough in eliminating fatalities and accidents in an accident prone industry. Possibly a better evaluation of this legislation lies somewhere in between. From the viewpoint of the coal industry it can be said that through the efforts of those engaged in mining, both the operator and the miner, the year 1969 marked a record year in mine safety with only 190 fatalities and a frequency of 0.84 per million man hours exposure. This outstanding achievement compared to any previous was the result of a determined effort on the part of a concerned industry to improve its reputation as being the most hazardous industry in the nation. After the effective date of the Act, March 31, 1970, the Bureau of Mines assumed complete control of all safety and health activities of the mining industry. Unfortunately, there was no improvement in the safety record of underground mines in 1970 with the total of 255 fatal injuries and a frequency of 1.04 for the year. The number of fatalities declined to 177 in 1971 but the number of underground coal mines had declined from 5,955 to 2,268 during the two year period. Meanwhile, surface mined coal increased from about 38% of total production in 1969 to over 50% in 1971, keeping the annual production of coal at a normal level but involving fewer men.